Bismuth embedded silica nanoparticles loaded with autophagy suppressant to promote photothermal therapy. (November 2019) - Chen, Tong; Cen, Dong; Ren, Zhaohui; Wang, Yifan; Cai, Xiujun; Huang, Jie; Di Silvio, Lucy; Li, Xiang; Han, Gaorong
Abstract: An unpredicted side effect of photothermal therapy (PTT) is agitated by hyperthermia which results in damage to healthy tissue. Developing PTT platforms, enabling effective tumor ablation under mild irradiation conditions, is of wide interest, but challenging. Here, we investigated bismuth crystals embedded silica (Bi@SiO2 ) nanoparticles, loaded with an autophagy inhibitor (chloroquine, CQ). It was found that SiO2 effectively prevented the oxidization of Bi nanocrystals in the physiological environment and could serve as a scatter layer to improve NIR absorption, enabling a high photothermal conversion efficiency ( 43%) and excellent photostability. Furthermore, the findings indicated that CQ molecules, delivered intracellularly by the particles, significantly weakened the degradation of autolysosomes by lysosome within the tumor cells, thus inducing suppression effect to autophagy and resistance to photothermia. Both in vitro and in vivo anti-tumor effects were consequently promoted owing to the combined effects enabled by Bi@SiO2 -CQ nanoparticles under mild NIR irradiation conditions. This study demonstrates a potential new PTT platform with superior therapeutic efficacy. Graphical abstract: Image 1